2021
DOI: 10.1371/journal.pone.0245243
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of the skin and gut microbiota in premenarchal vulvar lichen sclerosus: A pilot case-control study

Abstract: The etiology of vulvar lichen sclerosus (LS) remains unclear; however, alterations in cutaneous and gut microbiota may be contributing to the pathogenesis of this inflammatory condition. To explore this hypothesis, we conducted a pilot case-control study, obtaining dermal swab and stool samples from prepubertal girls with vulvar LS (n = 5), girls with nonspecific vulvovaginitis (n = 5), and healthy controls (n = 3). Samples (n = 56) were subjected to total DNA extractions. Resulting DNA was purified, subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 41 publications
1
23
0
2
Order By: Relevance
“…Gao et al found that the proportion of Blautia obeum, Faecalibacterium, Prevotella copri, Roseburia faecis, and Ruminococcus in the intestine of patients with colon cancer decreased in varying degrees (P < 0:05) [29]. Suhana et al tested the skin swabs and stool samples of 13 patients and found that lichen sclerosus may be associated with abnormal levels of Roseburia faecis and Ruminococcus [30]. We further studied whether the effect of TWBXG was achieved by regulating the disordered intestinal flora by treating 13 insomniac patients with TWBXG for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al found that the proportion of Blautia obeum, Faecalibacterium, Prevotella copri, Roseburia faecis, and Ruminococcus in the intestine of patients with colon cancer decreased in varying degrees (P < 0:05) [29]. Suhana et al tested the skin swabs and stool samples of 13 patients and found that lichen sclerosus may be associated with abnormal levels of Roseburia faecis and Ruminococcus [30]. We further studied whether the effect of TWBXG was achieved by regulating the disordered intestinal flora by treating 13 insomniac patients with TWBXG for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Chattopadhyay et al, in a pilot small-sample study ( n = 13), showed promising results in this matter. They suggest that there may be a relation between intestinal and cutaneous dysbiosis, and the disease in children, although this needs further investigation [ 22 ].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…It might be difficult to distinguish the lesions from those of morphoea. The clinical types of extragenital VLS include an extensive bullous form [ 19 , 21 ] and annular, blaschkoid and keratotic variants [ 22 ]. Koebnerization is very common at extragenital sites, arising at pressure points, old surgical and radiotherapy scars, and sites of trauma, including urostomies [ 18 ].…”
Section: Symptomsmentioning
confidence: 99%
“…A dysbiosis has been observed in the skin and gut microbiotas of LS subjects [91]. In particular, the bacterial genera Prevotella spp., Peptostrepococcus spp., Porphyromonas spp.…”
Section: Triggering Factorsmentioning
confidence: 99%